Tawarruq Application in Islamic Banking: A Comparative Study between Malaysia and Indonesia - Muhamad Yusuf Abdillah; Mighfari Elsha Rabi; Rizal Nazarudin Firli (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
Tawarruq contract is one of financing instrument or product used by Islamic banks in solving cash liquidity issue, but unfortunately this tawarruq contract is still debatable since the Islamic scholars have different views related to the ability of this contract. Some allow, and some do not allow. The Sharia Committees in Malaysia through their fatwa have approved and legitimated theapplicationof tawarruqin Islamic Banks. While in Indonesia, DewanSyariahNasional (The National Sharia Board) does not allow Islamic banks to use thistawarruq contract. This paper aims to make comparative studies between Indonesia and Malaysia in the application of tawarruq contract which has been practised in Islamic banking based on the qualitative data which will explore more on its back ground, view of Islamic scholars, and legal framework used by both countries i.e. Malaysia and Indonesia. Recently tawarruqis applicable in Malaysia but not in Indonesia. Despite Malaysia has been earlier in establishing Islamic Banking than Indonesia, however Indonesia and Malaysia have similarities in many things such as social, culture, historical and even madzhab.This paper also aims to analyze specific reason of DSN in relation of impermissible tawarruqused by Islamic banking in Indonesia.